Social and legal protection of child neglect and homelessness during quarantine - Сіньова, Людмила Миколаївна (Київський національний університет імені Тараса Шевченка, 2021)
The article examines the features of the legal status of child neglect and homelessness, determines the place of this category of persons in society and the state. Child neglect and homelessness are considered as a separate category that needs social and legal protection from the state and charitable organizations, especially during the coronavirus pandemic (COVID-19). Today, the problem of homeless people and homeless children in Ukraine distorts the social environment, destroys the physical, mental and spiritual health of people, reduces their vital, social and creative activity, worsens morale, as well as creates tension in society. The main reasons for this situation were a sharp decline in income and living standards due to the coronavirus pandemic (COVID-19) and structural changes in the economy, unprofitability of many manufacturing enterprises, imperfect financial and credit mechanisms, the sharp increase in existing and hidden unemployment, unpreparedness of training and social institutions, as well as law enforcement agencies to work with such categories of the population in the market conditions. The general principles of social protection of homeless persons and homeless children established by the legislation are determined. It provides legal regulation for relations in society, which are aimed at realization by homeless persons and homeless children of their rights and freedoms provided by the Constitution and legislation of Ukraine. It also creates conditions for public and charitable organizations working in the field of social protection. The conditions and active growth of the number of homeless people and homeless children during quarantine are studied. The author points out the need to comply with the current legislation in the field of social and legal protection of this category of persons, especially during quarantine, as health should be a strategic direction of human life. Thus, the state should protect and help homeless citizens and homeless children according to the Constitution of Ukraine, as a person, his life and health, honor and dignity, inviolability and security are recognized in Ukraine as the highest social value. The maintenance and upbringing of orphans and children deprived of parental care is the responsibility of the state. Keywords: homelessness, child neglect, life circumstances, health care, quarantine, social assistance, social services, orphanhood.

Досліджено особливості правового статусу дитячої бездоглядності та безпритульності й визначено місце зазначеної категорії осіб у суспільстві та діяльності держави. Дитяча бездоглядність та безпритульність розглядаються як окрема категорія, яка потребує соціально-правового захисту від держави та благодійних організацій, особливо в період пандемії коронавірусної хвороби (COVID-19). Нині проблема бездомних громадян і безпритульних дітей в Україні деформує соціальне середовище, руйнує фізичне, психічне та духовне здоров'я людей, знижує їхню життєву, громадську та творчу активність, погіршує моральний стан, створює соціальну напругу в суспільстві. Основними причинами такої ситуації стало різке зниження доходів і рівня життя населення внаслідок пандемії коронавірусної хвороби (COVID-19) і структурних змін у галузях економіки, збитковості багатьох підприємств виробничої сфери, недосконалості фінансово-кредитних механізмів, різкого збільшення наявного та прихованого безробіття, а також неготовність навчальних і соціальних закладів, правоохоронних органів проводити роботу з такими категоріями населення в ринкових умовах. Визначено закріплені законодавством загальні засади соціального захисту бездомних осіб і безпритульних дітей, що забезпечують правове регулювання у суспільстві відносин, які спрямовані на реалізацію бездомними особами і безпритульними дітьми прав і свобод, передбачених Конституцією та законодавством України, створено умови для діяльності громадських і благодійних організацій, що працюють у сфері соціального захисту населення. Досліджено умови й активне зростання чисельності бездомних громадян та безпритульних дітей під час карантину. Указано на необхідність дотримання й удосконалення чинного законодавства у сфері соціально-правового захисту зазначеної категорії осіб, особливо під час карантину, оскільки здоров'я має бути стратегічним напрямом усього життя людини. Таким чином, держава має захищати та допомагати бездомним громадянам і безпритульним дітям згідно з Конституцією України, адже людина, її життя і здоров'я, честь і гідність, недоторканність і безпека визнаються в Україні найвищою соціальною цінністю. Утримання та виховання дітей-сиріт і дітей, позбавлених батьківського піклування, покладається на державу.
Соціально-правовий захист дитячої бездоглядності та безпритульності під час карантину
Соціально-правовий захист дитячої бездоглядності та безпритульності під час карантину
Keywords: безпритульність; дитяча бездоглядність; життєві обставини; охорона здоров'я; карантин; соціальні послуги; сирітство; homelessness; child neglect; life circumstances; health care; quarantine; social assistance; social services; orphanhood